m-Learning: Positioning educators for a mobile, connected future - Peters, Kristine (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2007)
Mobile learning is variously viewed as a fad, a threat, and an answer to the learning needs of time-poor mobile workers, so does it have a place in delivering mainstream learning? Based on a 2005 comparative research project, commissioned by the Australian Flexible Learning Framework, the paper reports on research into Web-based information about the use of mobile technologies for commerce and learning, which was then tested through 29 interviews with manufacturers of mobile devices, businesses and education providers. The research found that mobile technologies were in common use in some commercial sectors, but their use purely for learning was rare. m-Learning lends itself to new methods of delivery, however, that are highly suited to the ‘just enough, just in time, and just for me’ demands of 21st Century learners.